2018
DOI: 10.21037/tcr.2018.02.07
|View full text |Cite
|
Sign up to set email alerts
|

New techniques for sentinel node biopsy in breast cancer

Abstract: Sentinel lymph node biopsy (SLNB) is still the standard of care for axillary nodal staging in patients with invasive breast cancer (BC) and clinically negative lymph nodes (LNs). It successfully replaced the more invasive and morbid axillary lymph node dissection (ALND). The actual standard for SLNB is the radioisotope (RI) with or without blue dye (BD) technique. Because of several drawbacks reported in worldwide experiences, new techniques have been developed in the last years: indocyanine green (ICG) fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 87 publications
0
26
1
1
Order By: Relevance
“…[2][3][4] Gold standard lymphatic mapping uses a combination of blue dye (BD; patent blue, methylene blue, or isosulphan blue) and radioactive colloid. [8][9][10][11] This dual tracer approach facilitates high sensitivity and low false negative rates. 9 However, BD can cause allergic reactions in 1.8% of patients, of which approximately 23% are type I hypersensitivity and 69% are type IV skin reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Gold standard lymphatic mapping uses a combination of blue dye (BD; patent blue, methylene blue, or isosulphan blue) and radioactive colloid. [8][9][10][11] This dual tracer approach facilitates high sensitivity and low false negative rates. 9 However, BD can cause allergic reactions in 1.8% of patients, of which approximately 23% are type I hypersensitivity and 69% are type IV skin reactions.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] This dual tracer approach facilitates high sensitivity and low false negative rates. 9 However, BD can cause allergic reactions in 1.8% of patients, of which approximately 23% are type I hypersensitivity and 69% are type IV skin reactions. 12 Additionally, BD can cause semi-permanent skin staining/tattooing, which may or may not fade after several months, 13 and the technique may fail to accurately identify all sentinel nodes when used in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Since many studies have shown a great variation in identification (IR) and false negative rates (FNR), the reliability of SLNB after neoadjuvant chemotherapy (NACT) remains questionable [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Performing axillary lymph node dissection as a substitute for sentinel lymph node biopsy even in the absence of radioisotope is no longer accepted. This explains the need for providing other effective alternatives for SLN detection in areas lacking availability of radioisotopes …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, depending on blue dye alone has some disadvantages such as the relatively lower identification rate, the need for cumulative surgeon experience, and the lack of possibility to locate the LN site before skin incision. This led to thinking about the need for developing other alternatives for SLN detection which can offer the same detection & accuracy rates and avoid the drawbacks of the already available methods …”
Section: Introductionmentioning
confidence: 99%